Membangun Karakter Siswa melalui Kesantunan Bahasa - Achadi Budi Santosa; Muhammad Zuhaery (UIR Press, 2021)
A person's character is very dependent on the environment in which they live and grow into adulthood. This study seeks to reveal one of the indicators of children's character, namely language politeness, especially in the school environment. The purpose of this study was to determine the reality of the condition of language politeness of children to their teachers and schoolmates, to find out the factors that cause language politeness deviations, and to find out the efforts made by schools in dealing with these deviations. This research is a qualitative research that produces descriptive data. Research subjects include teachers and students. The results showed that there were still some children who experienced deviations in language politeness to their teachers and school friends, namely in the form of reluctance to use polite language speech, mutual ridicule/verbal bullying between school friends using the names of parents and the profession of parents, and the unfavorable influence of social media.